Process of Data Visualization: Voyage from Data to Knowledge - Mahajan, Kirti Nilesh; Gokhale, Leena Ajay (International Journal of Computer Sciences and Engineering, 2019)
The voyage of data begins with collection of data, followed by storing this data in precise format, further traveling through the process of Data Analysis and Data Visualization, ultimately concluding the journey by reaching to valuable knowledge. Thus, this journey originates from Data, reaching to Knowledge. This original data has various dimensions, several logical formats like text, numbers and also physical structures such as structured, semi-structured and unstructured. The complexity of the data increases with the increased number of dimensions of data. During this entire journey, the data has to travel through various phases including Data Analysis and Data Visualization. However, the outcome of data analysis may not be adequate to provide the knowledge. Visualization Process involves seven steps, Acquire, Parse, Filter, Mine, Represent, Refine and Interact. Acquiring refers to obtaining the data, Parsing structures the data, Filtering allows to select the precise data, Mining supports in uncovering the patterns, Representing provides visual data, Refining allows to enhance the presentation of data, Interacting develops an interaction with the gained knowledge. Each phase makes data more meaningful as the process of data visualization contributes in enhancing the quality of the analysed data. Thus, role of visualization in this voyage is significant as it transforms data into knowledge. The purpose of this research paper is to describe the various phases in the process of data visualization along with several formats of original data and also presents comparison between data and information, before and after visualization.